Sexual activity in patients with left ventricular assist devices and their partners: impact of the device on quality of life, anxiety and depression. (2nd December 2017) - Kugler, Christiane; Meng, Michael; Rehn, Erik; Morshuis, Michiel; Gummert, Jan F; Tigges-Limmer, Katharina
Abstract: OBJECTIVES: Prolonged support with a left ventricular assist device (LVAD) has evolved as an alternative treatment strategy for patients with end-stage heart disease. This requires a shift in focus on sexual activity and psychosocial outcomes in patients with an LVAD and their partners. METHODS: This cross-sectional study was designed to capture Sexual Activities in Left Ventricular Assist Device Patients Or PaRtners (SALVADOR) perceptions on illness-related changes in the quality of sexual activity and its impact on quality of life, anxiety and depression using standardized patient-reported outcome scales (Sexual Adjustment Scale, 36-Item Short Form Health Survey, Hospital Anxiety and Depression Scale). A total of 72 patients with LVADs (50% response rate) along with 48 partners participated. RESULTS: For patients with an LVAD (median age 60 years; 84.7% male), median time on the device was 650 days; 69.5% stayed in long-term partnerships (median 23 years). Prevalence rates for illness-related changes in the quality of sexual activity were 58.3% for patients and 52.1% for partners. Device-related disturbances in sexual activities occurred due to battery pockets (patients/partners: 59.2%/37.6%; P = 0.006) and the driveline (46.3%/37.5%; P = 0.033) and led to significantly increased distress in patients/partners (battery pockets: 53.5%/41.3%; P = 0.006; driveline 54.9%/37.5%; P = 0.004). Disturbances in sexual activity were independently associated with higher rates of depression (odds ratio 1.33, 95% confidence interval 1.14–1.55; P = 0.001) in patients and lower mental quality of life (odds ratio 6.18, 95% confidence interval 1.13–33.98; P = 0.036) in partners. CONCLUSIONS: Disturbances in sexual activity are common in patients with an LVAD and their partners while the patients are on durable long-term support. Counselling on long-term adjustment should provide a platform for information seeking on illness-related changes in the quality of sexual activity.